Aspek Moral Tokoh dalam Dwilogi Novel Padang Bulan dan Novel Cinta Dalam Gelas Karya Andrea Hirata - Effendi, Putri Nia; Thahar, Harris Effendi; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article aimed to describe and explain the moral aspects of the characters in the novel Dwilogi Padang Bulan and the novel Cinta di Dalam Gelas by Andrea Hirata. The data of this study is novel text contained in the novel, taken in accordance with the research objectives. The data source of this research is novel Dwilogi Padang Bulan and the novel Cinta di Dalam Gelas by Andrea Hirata. Data collected by reading the novel Dwilogi first to get a clear picture of the content of the novel, and then described the data as advanced techniques. Research findings, namely that most of the characters in the novel Dwilogi already have good morale as reflected in the attitudes and behavior related to (1) conscience, (2) freedom and responsibility, (3) the rights and obligations, and (4) values ​​and norms.